2015
DOI: 10.1093/nar/gkv1167
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic fingerprints of ligand binding to human telomeric G-quadruplexes

Abstract: Thermodynamic studies of ligand binding to human telomere (ht) DNA quadruplexes, as a rule, neglect the involvement of various ht-DNA conformations in the binding process. Therefore, the thermodynamic driving forces and the mechanisms of ht-DNA G-quadruplex-ligand recognition remain poorly understood. In this work we characterize thermodynamically and structurally binding of netropsin (Net), dibenzotetraaza[14]annulene derivatives (DP77, DP78), cationic porphyrin (TMPyP4) and two bisquinolinium ligands (Phen-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 65 publications
6
44
0
Order By: Relevance
“…Remarkably, all PDC–fluorophore conjugates are able to induce conformational changes of hybrid G4‐DNA structures derived from a human telomeric sequence (22AG, 25TAG, 24TTG), namely a conversion to an antiparallel structure evidenced by CD spectroscopy. This behavior has already been documented for PDC and other ligands of bisquinolin(ium) series (360A‐Br, PhenDC 3 , pyridostatin), although the details of this process and the structure of the resulting ligand‐G4 complex are still not clear . Compared with PDC‐L , the effect of the conjugates on this conformational change is somewhat less pronounced.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Remarkably, all PDC–fluorophore conjugates are able to induce conformational changes of hybrid G4‐DNA structures derived from a human telomeric sequence (22AG, 25TAG, 24TTG), namely a conversion to an antiparallel structure evidenced by CD spectroscopy. This behavior has already been documented for PDC and other ligands of bisquinolin(ium) series (360A‐Br, PhenDC 3 , pyridostatin), although the details of this process and the structure of the resulting ligand‐G4 complex are still not clear . Compared with PDC‐L , the effect of the conjugates on this conformational change is somewhat less pronounced.…”
Section: Discussionmentioning
confidence: 76%
“…Binding of ligands to G‐quadruplex structures may induce conformation changes of the latter, due to a particular ligand's affinity to one or another quadruplex fold. The most prominent example of this transformation is the shift from hybrid conformations adopted by the human telomeric sequence (22AG) in K + ‐rich conditions to an antiparallel form, induced by PDC and other ligands belonging to the dicarboxamide series . To assess this phenomenon, we compared CD spectra of several G4‐DNA structures belonging to different topological groups in the absence and in the presence of two molar equivalents of PDC‐L , PDC‐L2‐PY , and three PDC‐coumarin conjugates differing in linker length ( PDC‐L1‐C2 , PDC‐L2‐C2 , PDC‐L3‐C2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These differences in binding thermodynamics between the different ligands indicate that besides the NDI scaffold, the side chains play an important role in binding to the oligonucleotide. Furthermore, binding of imidazolium‐glycoside 3 , imidazolium 5 and methylpiperazine 6 to telo23 K + is greater than that of cationic porphyrin TmPyP4 as measured by Bončina et al., and of a similar magnitude as that of the quadruplex ligand Phen‐DC3 …”
Section: Figurementioning
confidence: 68%
“…Indeed, the characterization of ligand binding to G-quadruplexes should not be limited to binding affinity, but should also consider ligand-induced changes in the target conformation. It was recently shown that the binding of some of the most potent ligands known to date (360A, Phen-DC3 and pyridostatin) was accompanied by the ejection of one cation (85,86), suggesting that the ligands preferentially bind to 2-quartet antiparallel structures. Species that are off-pathway in the folding of model oligonucleotides in vitro can become the predominant species in another environment.…”
Section: Resultsmentioning
confidence: 99%